Nanodelivery of gambogic acid by functionalized graphene enhances inhibition of cell proliferation and induces G0/G1 cell cycle arrest in cervical, ovarian, and prostate cancer cells. Issue 55 (17th June 2015) - Saeed, L. M.; Mahmood, M.; Xu, Y.; Nima, Z. A.; Kannarpady, G. K.; Bratton, S. M.; Dervishi, E.; Casciano, D.; Ali, S.; Crooks, P. A.; Radominska-Pandya, A.; Biris, A. S.
<x xml:space="preserve">Abstract</x> Graphene was used to deliver gambogic acid to cervical, ovarian, and prostate cancer cells and the complex was shown to be more effective at inhibiting cell proliferation, initiating cell cycle arrest and inducing apoptosis compared to the drug alone.